Europe’s anthem and its meaning - Januszewska-Warych, M. (Світогляд - Філософія - Релігія, 2012)
The article presents research on the anthem of the Europe. The author investigates its origins, argues about other possible variants for the Europe’s anthem, and provides critical analysys of the meaning, functions and prospects of the Ode to Joy.